2017
DOI: 10.1111/plb.12533
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic tobacco plants constitutively expressing peanut BTF3 exhibit increased growth and tolerance to abiotic stresses

Abstract: Abiotic stresses limit crop growth and productivity worldwide. Cellular tolerance, an important abiotic stress adaptive trait, involves coordinated activities of multiple proteins linked to signalling cascades, transcriptional regulation and other diverse processes. Basal transcriptional machinery is considered to be critical for maintaining transcription under stressful conditions. From this context, discovery of novel basal transcription regulators from stress adapted crops like peanut would be useful for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Betweenness centrality exhibited an opposite pattern. In the networks modeled for the hybrids, genes with high betweenness were mostly associated with protein synthesis and gene expression regulation, including the protein translation factor SUI1 (Li et al 2022), the transcription factor BTF3 (Pruthvi et al 2017), and the calcium/calmodulin-regulated receptor-like kinase 1 (Yuan et al 2022). In contrast, the network modeled for S. spontaneum had genes with high betweenness primarily associated with cellular structure and division, such as the kinetochore-associated protein KNL-2 (Zuo et al 2022) and formin-like protein (Kollárová et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Betweenness centrality exhibited an opposite pattern. In the networks modeled for the hybrids, genes with high betweenness were mostly associated with protein synthesis and gene expression regulation, including the protein translation factor SUI1 (Li et al 2022), the transcription factor BTF3 (Pruthvi et al 2017), and the calcium/calmodulin-regulated receptor-like kinase 1 (Yuan et al 2022). In contrast, the network modeled for S. spontaneum had genes with high betweenness primarily associated with cellular structure and division, such as the kinetochore-associated protein KNL-2 (Zuo et al 2022) and formin-like protein (Kollárová et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…2013; Pruthvi et al . 2017). The bZIP family is one of the most widely distributed and conserved TFs in eukaryotes and is crucial in responses to abiotic stress (Riechmann & Ratcliffe 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The protein-protein interaction network revealed that BTF3 was clearly affected by air PM. This gene in known to be induced to salt stress and the transgenic expression of BTF3 enhances tolerance of transgenic plants to reactive oxygen species (ROS) through the activation of scavenging activity, enhancing higher cell membrane stability and seedling survival under osmotic stress (Pruthvi et al, 2017). BTF3 is also involved in the modulation of cold stress response.…”
Section: Protein-protein Interaction Network In Response To Pmmentioning
confidence: 99%